Pengembangan Platform Evaluasi Digital Literasi Sains Pada Sistem Pencernaan Manusia - Rosaliana, Mela; Yuniarti, Yeni; Sukardi, Rendi Restiana (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is motivated by technological developments in the world of education where the learning process, especially learning evaluation, is time to be integrated with the use of digital technology. The purpose of this study was to analyze digital literacy-oriented evaluation of digestive material science literacy in humans in elementary schools using qualitative methods. This evaluation analysis uses the Plickers platform. This research involved one teacher and forty-five students from one of the public elementary schools in Bandung regency. One teacher and fifty students were selected based on a purposive sampling technique. The instruments used in this study include the use of interview sheets and observation sheets. The findings from this study indicate that elementary school teachers have not fully mastered technology and integrated it into the learning process, especially in the implementation of in-class learning evaluations, students feel bored and tense when implementing science learning, especially when conducting evaluations in class. The teacher also has not developed questions using a framework that hones students' literacy skills. Keywords: 1st Digital Evaluation; 2nd Elementary school; 3rd Digestive System In Humans.